Students' Perception of Podcast Integration in Listening Comprehension Learning - Zihori Maulida; Sudiani; Nicolás Girado (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
This study investigates student perceptions of podcast use in listening comprehension at Institut Pendidikan Nusantara Global. Thirty-five students completed a five-point Likert questionnaire covering accessibility, motivation, content effectiveness, and technical issues. Results show high scores for flexibility (mean 4.52) and motivation (4.33), while technical barriers remain (2.89). Thematic analysis of open responses revealed two themes: learner autonomy and content mismatch. The findings highlight podcasts’ potential to foster independent and engaged learning but emphasize the need for improved infrastructure and better-aligned content.